Financing Models and Affordable Housing in Kenyan Real Estate - Kinya, Mbaabu Brenda (University of Embu, 2020)
Approximately 100 million people are homeless in the world, in Kenya 2 million are homeless and more living in slums. With the continuous population increase in the country, the real estate market needs to increase the supply of houses in the country and make them affordable to all caliber of people inclusive of low-income people. Kenya recognizes housing in its vision in 2030 as one of the pillars also in the constitution (2010) the bill of rights provides that everyone has a right to access adequate housing. Means of financing a home includes the use of loans, joint ventures, and pooling of individual funds these means have to make sure that they are available to all. The main aim of this study is to address the problem we have in the country which is unaffordable housing. The financing models available are not achieving affordable housing and thus why many are living in poor conditions. The objectives of the study are determining the availability of mortgage loans, the influence of interest rates on mortgages, and finally, the uptake of pension backed housing. The study adopts the use of secondary data and using descriptive statistics to analyze the findings in order to draw a conclusion. The findings of the study are that mortgage loans are not available to low-income households because of their requirements they hinder the low-income society from affording them. The low-income households do not a stable income to manage the interest rates set and to manage the loan size. The uptake of pension backed housing is low cause there is inadequate awareness of the pension backed housing means and the savings culture of the people is quite wanting. Interest rates have an influence on mortgage loans and they have a negative impact and it can be argued that they do increase the default cases of mortgages. Restructuring of the mortgage loan is crucial in helping that the loans are available to the low-income households, the pension backed house financing method has to be publicized more to increase the awareness more and the interest rates we have to see the effect of removing the cap rate on the loans what effect it will have if it’s better than its absence.